O (DES) VALOR DO TRABALHO DOMÉSTICO E O JULGAMENTO SOB A PERSPECTIVA DE GÊNERO: UMA ANÁLISE JURÍDICA SOBRE AS SEGURADAS FACULTATIVAS (DO LAR) E ESPECIAIS (TRABALHADORAS RURAIS E PESCADORAS) - Priscila Guimarães Marciano (2025)
The 1988 Constitution promoted formal gender equality, rejecting discrimination between men and women. Following this trend, laws were enacted that provide for the payment of wages in cases of old age, temporary or permanent disability, and other benefits, without distinction of gender. Despite these legal achievements, rural workers and artisanal fisherwomen (both special insured) and housewives (optional insured) face barriers in accessing social security benefits, especially in producing evidence of the performance of their domestic activities. Given this scenario, this research presents the following problem: Would the use of a judgment from a gender perspective be sufficient to remove or reduce the obstacles to access to the enjoyment of social security rights by rural workers, fisherwomen, and homemakers? The general objective is to analyze whether the adoption of a protocol with a gender perspective would be able to eliminate or reduce the barriers to access to the enjoyment of social security rights by rural workers, fisherwomen, and homemakers. The specific objectives are: to highlight the main barriers that rural workers, artisanal fisherwomen and domestic workers face in accessing social security rights; to examine theories about the devaluation of domestic work; and to explore the application of the Protocol for judgment with a gender perspective in the granting of social security benefits to rural workers, artisanal fisherwomen and domestic workers. To this end, the research is bibliographical, qualitative, theoretical, and descriptive in nature, focused on an analysis of social processes and relations. The methodological approach adopted also favors the analysis of social security case studies involving the research theme selected from the website of the Federal Justice Council (by sampling) and the Regional Court of the 3rd Region. The cases are important to help understand the study proposal and were researched via a keyword search system, using the search terms “gender perspective”, “optional” and “do casa”; in addition to “rural worker” and “retirement by age” and “fisherwoman”, with preferences for the most recent judgments, between the years 2019 and 2024. The date chosen encompasses judgments before and after the adoption of the Protocol (CNJ Resolution 492/2023) for the analysis of changes in the guidelines in the judgments. The CJF website was chosen because it concentrates federal jurisprudence in a unified manner and has a reliable search tool. In addition, the TRF3 website was selected because it houses one of the largest courts in the country, the judicial section of São Paulo, which facilitates the search and offering of cases. The selection of cases aims to verify the presence of gender stereotypes and the invisibility of the insured women, who, although they fit into different categories, have in common the fact that they are homemakers. Finally, this study relies on the author's participant observation in the Federal Itinerant Court in Pantanal communities in Mato Grosso do Sul, in the years 2022 and 2023.